PERAN GURU/ PENDAMPING DALAM MENGEMBANGKAN SIKAP POSITIF ANAK USIA DINI YANG DITINGGAL ORANG TUA MENJADI TKW DALAM PERSPEKTIF BIMBINGAN DAN KONSELING - Siti Khomsiyati (AZZAHRA, 2019)
Mother is expected to be a figure who is always present in every journey of growth and development of her children with Dad who is a role model and backbone figure in the family. Not a few children at an early age left by their mothers to become migrant workers experience problems related to psychological development, especially those related to positive attitudes including; lack of confidence such as wanting to always be accompanied by the guardian of his students, likes to do naughty to his friends, speak loudly and not well, like to seek attention by making noise in the classroom, this is an important concern for kindergarten teachers as educators to be able optimally carry out its role and function not only as a teacher but also as a substitute for parents at school. This article is a descriptive qualitative research method. As for the roles that have been carried out by the teacher / companion in Braja Indaah Islamic Kindergarten in developing the positive attitude of their students including conducting a need assessment, carrying out information services, individual counseling services, and home visits.